2018
DOI: 10.1111/petr.13188
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of medication non‐adherence in pediatric organ transplantation: A systematic review

Abstract: Adherence to immunosuppressant medication is critical to health and quality-of-life outcomes for children who have received a solid organ transplant. Research on the psychological and social predictors of medication adherence is essential to the advancement of pretransplant assessments and transplant psychosocial services. Despite the importance of identifying risk factors, the literature remains limited regarding psychosocial predictors of non-adherence. A systematic search was conducted to identify studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 97 publications
(335 reference statements)
1
98
1
Order By: Relevance
“…Demographic variables (ie, age of child and income) were entered into the first step of the regression based on theory positing that developmental age and family resources can impact adherence. Research has demonstrated that older adolescents and lower income families exhibited greater non‐adherence. The current sample supports this relationship, as the age of the child was significantly related to missed doses and income level to late doses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographic variables (ie, age of child and income) were entered into the first step of the regression based on theory positing that developmental age and family resources can impact adherence. Research has demonstrated that older adolescents and lower income families exhibited greater non‐adherence. The current sample supports this relationship, as the age of the child was significantly related to missed doses and income level to late doses.…”
Section: Resultsmentioning
confidence: 99%
“…The first hypothesis was examined utilizing a hierarchical multiple Research has demonstrated that older adolescents 1,22 and lower income families 21,22 exhibited greater non-adherence. The current sample supports this relationship, as the age of the child was significantly related to missed doses and income level to late doses.…”
Section: Family Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Medication non‐adherence is especially prevalent in adolescent transplant populations with an estimated non‐adherence rate of 15%‐40% . Factors associated with non‐adherence in this population are extensive and include low socioeconomic status, family instability, limited parental supervision, depression, poor coping, disease frustration, longer time since transplant, side effects associated with immunosuppressive medication, and poor knowledge about the risks of medication non‐adherence …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Factors associated with non-adherence in this population are extensive and include low socioeconomic status, family instability, limited parental supervision, depression, poor coping, disease frustration, longer time since transplant, side effects associated with immunosuppressive medication, and poor knowledge about the risks of medication non-adherence. 5,11,12 Researchers have studied numerous direct and indirect methods to assess medication adherence in pediatric patients. 2,13 Direct methods include observing a patient taking a medication and/or measurements of patients' blood levels and result in a highly accurate estimate of medication adherence.…”
Section: Introductionmentioning
confidence: 99%